Interprofessional Collaborative Relationship-Building Model in Action in Primary Care: A Secondary Analysis - Pamela Wener; Leanne Leclair; Moni Fricke; Cara Brown (Frontiers Media S.A., 2022)
IntroductionTeam-based care has been integrated into primary care (PC) across Canada because it improves patient safety, effectiveness, efficiency, person-centredness, and equity. However, this integration in and of itself may not lead to improved patient care without effective interpersonal relationships amongst team members. Currently, teams have few tools to guide the development of collaborative relationships. The Interprofessional Collaborative Relationship-building Model (ICRB) was developed to be a tool for understanding the stages of development of the interprofessional team's relationship-building.PurposeThis qualitative secondary data analysis illuminates a PC team's experiences of their developing interprofessional relationships with occupational therapists and physical therapists who joined the PC team.MethodEleven team member interviews of one primary care team from a family medicine teaching clinic affiliated with a training university and the health region in central Canada were analyzed using secondary data analysis. The team included family physicians (n = 4), nurses (n = 2), a social worker (n = 1), a mental health counselor (n = 1), occupational therapists (n = 2), and a physical therapist (n = 1). We used the ICRB for directed content analysis using the phased approach that includes the three main steps of data preparation, data organization and data presentation.ResultsThis team experienced the ICRB stages of Looking For Help, Fitting-In, and Growing Reciprocity thereby learning about one another to better understand what OT and PT may bring to the PC setting. However, contrary to the ICRB, co-location, was the context within which the collaborative relationship-building took place rather than a distinct developmental stage. Although team members did experience some level of Growing Reciprocity, this developing team had not yet established collaborative leadership processes. As the ICRB originally posited, communication and patient focus facilitated all stages of the relationship-building process and helped the team develop shared values and role clarity that establish how different team members contribute to improving quality care.ConclusionsThe context of co-location with a patient focus and open communication facilitated the team's development with the occupational therapists and physical therapist. Collaborative leadership is a worthy goal for future research and clinical focus as it has implications for improving overall patient quality care and team member work satisfaction.